Speech Acts Analysis on King Charles III’s First Speech as the King of England and the Commonwealth Countries - Nurlaili, Iva (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2024)
After Queen Elizabeth II passed away, Prince Charles was officially crowned King Charles III, the King of England and the Commonwealth countries. In his first public speech as a king, delivered at Buckingham Palace on September 9, 2022, he expressed deep sorrow over the Queen’s passing, paid tribute to her lifetime of service as a queen, and pledged his dedication to the nation and the Commonwealth. This speech serves as a significant moment, marking the transition of leadership and strengthening the monarchy’s role in modern society. This study's aim is to find out the types of illocutionary acts in King Charles III’s first speech by using Searle’s Speech Acts Theory. This study uses a descriptive qualitative research design. The study examines the official speech transcript to identify and categorize the speech acts used. The findings reveal 43 instances of illocutionary acts, which are divided into four categories: assertive, commissive, expressive, and declarative. These speech acts provide multiple functions, including expressing personal emotions, affirming commitments to the people, and reinforcing the monarchy's authority. The results of this study highlight the strategic use of language in royal speech. Understanding the illocutionary aspects of King Charles III’s speech contributes to a broader analysis of political communication and pragmatics in leadership discourse.